Dom Casmurro, de Machado de Assis, para uma nova visão do amor-traição: um enfoque da linguística sistêmico-funcional - Silveira, Gustavo Cardoso (2023)
Meanings are not frozen entities but are generated and regenerated to the extent that they are immersed in the processes and structures that they constitute, on the one hand, and, while they are constituted by them, on the other hand. One can examine language as discourse, i.e., as text under social conditions of production and interpretation, to be independently examined since the text is subordinate to them; But these conditions can also be revealed through a linguistic analysis, employing all the methods and instruments that the discipline offers. Thus, while paying attention to the lexicogrammatical structures of the text, certain assumptions are verified that, although they do not form part of the formal structure of the text, are aspects of interpretation surreptitiously insinuated in the discourse. This doctoral thesis ex amines the construction of the characters Capitu, Bentinho and Escobar, from the novel Dom Casmurro, by Machado de Assis, and does so, following the slow process of accumulation of indicial traits of behaviors and dialogues that tend to confirm a certain inference, while allowing another. In this context, apart from the fact that a text reconstructs a certain version of reality, lexicogrammatical structural choices can be seen as a slow and discrete transformer of one style into another, by feeding the construction of a conceptual, global, and revealing metaphor. This pervasive and diffuse metaphor ensures the understanding of the text in a certain ideological perspective. The analysis has the support of Systemic-Functional Linguistics, a theoretical-methodological proposal that relates the microstructure of the choices made in the text to the macrostructure of the relations of force and ideology in the discourse and that involves the notions of Transitivity and Appraisal, important to reveal the underlying position of Machado de Assis in relation to the Bentinho-Capitu couple in their coexistence with Escobar. To this end, this research must answer the following questions: (a) what can the analysis of lexicogrammatical choices regarding the description of Capitu's behavior reveal, as well as those of Bentinho and Escobar? (b) in this process, what is the contribution of transitivity analysis and Appraisal? (c) what can the analysis of metaphor and its relation to metonymy reveal? The analysis shows that the metaphors of the wolf, the fox and the lamb originate in the extremely detailed description of these animals that ends up superficializing the truth that hides in the depths of being. It could be said that the reunion of three characters, each carrying their characteristic profile, could only result in what some still do not believe. If this were not the case, Machado would not have written Don Casmurro, the way he did